2022
DOI: 10.3389/fimmu.2022.939311
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and immune-persistence of the CoronaVac or Covilo inactivated COVID-19 Vaccine: a 6-month population-based cohort study

Abstract: BackgroundOwing to the coronavirus disease 2019 (COVID-19) pandemic and the emergency use of different types of COVID-19 vaccines, there is an urgent need to consider the effectiveness and persistence of different COVID-19 vaccines.MethodsWe investigated the immunogenicity of CoronaVac and Covilo, two inactivated vaccines against COVID-19 that each contain inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The levels of neutralizing antibodies to live SARS-CoV-2 and the inhibition rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Therefore, studies have also evaluated whether booster doses would provide additional protection to individuals vaccinated with CoronaVac. This strategy is supported by the fact that the antibody response elicited by CoronaVac has been found to wane following the second dose, though it was still detected 6 months out ( 83 ). A phase I/II clinical trial of CoronaVac in an elderly cohort (adults 60 years and older) in China determined that by 6 to 8 months following the second dose, nAb titers were detected below the seropositive cutoff ( 84 ).…”
Section: Inactivated Whole-virus Vaccinesmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, studies have also evaluated whether booster doses would provide additional protection to individuals vaccinated with CoronaVac. This strategy is supported by the fact that the antibody response elicited by CoronaVac has been found to wane following the second dose, though it was still detected 6 months out ( 83 ). A phase I/II clinical trial of CoronaVac in an elderly cohort (adults 60 years and older) in China determined that by 6 to 8 months following the second dose, nAb titers were detected below the seropositive cutoff ( 84 ).…”
Section: Inactivated Whole-virus Vaccinesmentioning
confidence: 90%
“…Studies have also investigated expected differences in real-world effectiveness of Covilo given the continuing evolution of SARS-CoV-2. The antibody response elicited by Covilo was found to wane, but to still be detectable, by 6 months following the second dose ( 83 ). One study showed that the Alpha variant exhibited very little resistance to neutralization by sera of those immunized with Covilo, but the Beta variant was more resistant to neutralization by almost a factor of 3 ( 81 ).…”
Section: Inactivated Whole-virus Vaccinesmentioning
confidence: 99%
“…Moreover, the mean efficacy of Covaxin is 61.80% against all variants of COVID-19 (Table 3; Figures 2 and 3). Neutralizing antibodies to live SARS-CoV-2; 77.9% seroconverted was by 28 days after the second dose [17] Two doses of vaccines with an interval of 28 days showed 95.0% seropositivity to anti-spike antibodies. [18,19] Local adverse effects Pain at the injection site, redness, [20] Injection site pain (41.5%) [21] Injection site pain, swelling, redness, and itching [15].…”
Section: Contraindicationsmentioning
confidence: 94%
“…1,29,30 In contrast, specific IgG antibodies following vaccination against SARS-CoV-2 are detectable from about a week following the first dose and peak at approximately 30 days after the second dose, remaining detectable for 3-6 months. 31,32 For example, a cross-sectional study in 56,261 Chilean individuals reported an IgG seroprevalence of 28.1% three weeks after the first dose and 77.4% four weeks after the second dose of the CoronaVac vaccine; and a prevalence of 79.4% three weeks after the first dose and 96.5% four weeks after the second dose of the BNT162b2 Pfizer vaccine. 7 In healthcare workers (HCW) receiving the BNT162b2 Pfizer vaccine, a study showed that median serum levels of antibodies reached a peak 1 month after the second dose and were 37% and 57% lower at 3 and 6 months, respectively.…”
Section: Discussionmentioning
confidence: 99%